Mangrove ecosystem provisioning services for the sustainability and diversity of bird species in the coastal region of Lombok Island, Indonesia (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Syukur A, Zulkifli L, Mahrus H. 2021. Mangrove ecosystem provisioning services for the sustainability and diversity of bird species in the coastal region of Lombok Island, Indonesia. Biodiversitas 24: 1589-1599. Ecological services offered by mangroves are imperative for various faunal species. The present study is focused on assessing the role of mangroves in the sustainability and diversity of bird species in the coastal region of Lombok Island, Indonesia. The aims of the study are (i) to describe the conservation status of bird species and (ii) to describe the value of the ecological index of birds as an indicator of mangrove conservation. The species diversity of birds is assessed by observation, whereas the quadratic transect method is used to assess mangrove vegetation structure. Data analysis has been carried out using univariate statistical analysis, namely the Shanon-Wiener index (H'), Simpson Index (d), Evenness Index (E), Richness Index (R), and linear regression analysis. The genus Rhizophora and Avicennia species have an even distribution in the study area. Rhizophora species in the study area result from revegetation, whereas Avicennia species grow naturally. Altogether, a total of 19 bird species have been observed in the present study. Of these, eight species have a limited distribution, four bird species are Near Threatened (NT), and others are Least Concern (LC) concerning their conservation status. The estimated Diversity Index (H') is ranged between 3.09-3.67, whereas Evenness (E) and Richness (R) index are ranged between 0.72-0.85 and 7.09-10.33, respectively. The ecological index value shows that the research locations have high species diversity and richness, and species are evenly distributed across the sites. Therefore, the value of the index of bird ecology and the distribution of bird species are indicators of mangrove supply services for the preservation of birds at the study site. The study concluded that the diversity of ecological indices and the conservation status of birds are important information for the success of mangrove conservation through revegetation at the study site. However, a comprehensive study is needed on the functional relationship of mangrove supply services with the diversity of bird species to obtain validity and rehabilitation as conservation indicators.